Paciente de sexo femenino de 27 años de edad con diagnostico lupus eritematoso sistémico - Kenlly Katherine, Cedeño Zambrano (2018)
The systemic lupus erythematosus considered as an inflammatory disease, characterized by the systemic damage that originates in the organism, that is, it can affect any part of the organ or system, being factors such as genetics, environment and hormones, represented by the presence of lymphocytes and immune complexes causing damage in inflammatory processes. (Martinez, Gutierrez, Zuñiga, Sanchez, 2015) When the lupus is triggered in the organism or system the immune system confuses and can not differentiate between foreign particles and cells or tissues which causes antibodies to be produced against itself causing inflammation and damaging tissues. (Comodo, 2017) KEYWORDS ERITEMATOSO ATRALGIAS MENINGITIS